2000
DOI: 10.1159/000054136
|View full text |Cite
|
Sign up to set email alerts
|

Formation, Inhibition and Clearance of Plasmin in vivo

Abstract: A 5 µg/kg bolus of tissue plasminogen activator (t-PA) was infused into 11 healthy subjects followed by measurement of t-PA activity and antigen, PAI-1 activity and antigen, t-PA/PAI-1 complex, plasmin/antiplasmin (PAP) complex and D-dimer over 4 h. Infusion of t-PA resulted in a rise in PAP levels in all subjects from a baseline of 2.4 ± 1.1 nmol/l to a peak of 5.1 ± 2.3 nmol/l, but had no effect on plasminogen, antiplasmin or D-dimer levels. Using a kinetic model of plasminogen activation in vivo, the second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…Third, the model system is critical since it allows specific assumptions to be defined, tested, and used in analysis and interpretation; allows kinetic processes to be directly compared, such as thrombin versus fibrin generation; and allows kinetic interactions to be studied, as we have done in the fibrinolytic system. 8,9 In this study we determined that the process of open-heart surgery utilizing CPB had different effects on thrombin and fibrin generation. At baseline prior to starting surgery, the average thrombin generation rate was about 0.24 picomoles of thrombin per second.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the model system is critical since it allows specific assumptions to be defined, tested, and used in analysis and interpretation; allows kinetic processes to be directly compared, such as thrombin versus fibrin generation; and allows kinetic interactions to be studied, as we have done in the fibrinolytic system. 8,9 In this study we determined that the process of open-heart surgery utilizing CPB had different effects on thrombin and fibrin generation. At baseline prior to starting surgery, the average thrombin generation rate was about 0.24 picomoles of thrombin per second.…”
Section: Discussionmentioning
confidence: 99%
“…The vascular model used in this study is a modification of previous models that were used to assess changes in fibrinolytic marker levels and to evaluate the effect massive blood loss has on fibrinolysis during liver transplantation. [8][9][10][11] As a clinical problem we chose to study coagulation during cardiopulmonary bypass (CPB) for several reasons: (1) CPB results in a reproducible stimulation of coagulation that can be used to study the regulation of this system, 12 (2) CPB is an important clinical tool used in the treatment of heart disease that still has significant risk and side effects associated with it, and (3) many new drugs (such as aprotinin) and technologies (such as heparin-coated bypass circuits) are being developed and used to reduce hemostatic activation and side effects, even though their precise mechanism of action is still debated. 13 The long range goal is to use this method of analysis to better understand the regulation of the hemostatic system and to hopefully suggest which new therapies are likely to be the most effective in preventing, suppressing, or eliminating hemostatic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…62 Raza et al demonstrated in 303 trauma patients that fibrinolytic activation as detected by elevated PAP levels is common (59% of patients), but hyperfibrinolysis as detected by ROTEM (5%) was not. 63 Given that PAP clearance has a half-life of 3 to 6 hours in healthy individuals, 64 many patients with elevated PAP levels may not have had ongoing elevation of fibrinolytic activity at the time of ROTEM assay. Increasing PAP levels were nonetheless independently associated with increased mortality, with the combination of elevated PAP level and ROTEM lysis being particularly deadly (40% mortality).…”
Section: Trauma-induced Coagulopathy 1045mentioning
confidence: 99%
“…In the absence of tPA, plasminogen bound to macrophage plasma membrane undergoes autoproteolysis generating a 48-kd inactive fragment with surface-binding capacity and small soluble fragments with catalytic capacity 37 that are rapidly inhibited in the fluid phase by anti-plasmins ( Figure 6). 38,39 The timing of AIIt involvement in fibrin degradation is also a crucial factor in promoting or inhibiting fibrinolysis because the presence of AIIt during fibrin polymerization inhibits fibrinolysis. 40 Therefore, limited availability of tPA in MS lesions because of formation of tPA-PAI-1 complexes as previously shown by nonreducing immunoblots of the same set of samples 31,41 reduces the ability of AIIt to generate plasmin and further diminishes the fibrinolytic capacity possibly resulting in increased axonal fibrin deposition and neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%